1994
DOI: 10.1093/hmg/3.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Human microsomal epoxide hydrolase: genetic poloymorphism and functional expression in vitro of amino acid variants

Abstract: Human microsomal epoxide hydrolase (mEH) is a biotransformation enzyme that metabolizes reactive epoxide intermediates to more water-soluble trans-dihydrodiol derivatives. We compared protein-coding sequences from six full-length human mEH DNA clones and assessed potential amino acid variation at seven positions. The prevalence of these variants was assessed in at least 37 unrelated individuals using polymerase chain reaction experiments. Only Tyr/His 113 (exon 3) and His/Arg 139 (exon 4) variants were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
348
2
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 450 publications
(367 citation statements)
references
References 24 publications
16
348
2
1
Order By: Relevance
“…In a mutagenesis study, Hasset et al (8) suggested that the protection effect could be due to the 'allelic selection' of gene expression. By showing that high activity mEH with Tyr113 exon 3 /Arg139 exon 4 was barely detected in NSCLC patients, our results indicated that selection pressure could be from air pollution, in particular, cigarette smoking or heavy oil fumes from the traditional Chinese cooking method (such as frying fish) (26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a mutagenesis study, Hasset et al (8) suggested that the protection effect could be due to the 'allelic selection' of gene expression. By showing that high activity mEH with Tyr113 exon 3 /Arg139 exon 4 was barely detected in NSCLC patients, our results indicated that selection pressure could be from air pollution, in particular, cigarette smoking or heavy oil fumes from the traditional Chinese cooking method (such as frying fish) (26).…”
Section: Discussionmentioning
confidence: 99%
“…When 295-and 62-bp fragments appeared, the patient had homozygous allele of His139. When 174-, 121-and 62-bp bands appeared, the patient was identified as homozygous Arg139 allele, and when all four DNA fragments appeared, the patient was heterozygous with His139/Arg139 (1,(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All DNA samples were genotyped for 25 SNPs of 18 XME genes by PCR-restriction fragment length polymorphism (RFLP) assays according to the array protocols available from the publications. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Supplementary Table 3 shows SNPs that have been analyzed in the study. PCR was performed in a final volume equal to 25 ml of reaction mixture containing 1.5 U of thermostable Taq DNA polymerase (Lytech, Moscow, Russia), B1 mg DNA, 0.25mM of each primer, 250 mM of dNTPs, 1.5-3.5 mM of MgCl 2 and 1Â PCR buffer (67 mM Tris-HCl pH 8.8, 16.6 mM (NH 4 ) 2 SO 4 , 0.01% Tween-20).…”
Section: Genotypingmentioning
confidence: 99%